Analisis Efisiensin Lembaga Amil Zakat (LAZ) di Indonesia Menggunakan Data Envelopment Analysis (DEA) Periode 2012-2013 - Novia Mawaryani, Arum, Eni Setyowati, SE, M.Si, Dr. Imron Rosyadi M.Ag (2016)
The objective of this research is to determine the level of efficiency Amil Zakat institution in Indonesia, both in their channel and raise zakat funds. The object of this research includes three agencies namely Rumah Zakat, Dompet Dhuafa, Pos Keadilan Peduli Umat (PKPU) in period year 2012-2013. The researcher used Data Envelopment Analysis (DEA) which analyzes the level of afficiency of the usage of inputs and outputs that are generated using secondary data obtained from financial reports that have been published on the official website of each institution amil zakat. Based on the calculations of DEA, amil zakat as the distributing agencies in period year 2012-2013 there is one institution that is not efficient in 2013, namely Rumah Zakat. While the other agencies have been efficient. Unfortunately, Amil Zakat Institution as collecting funds in period year 2012-2013 there is still inefficient institution, namely Rumah Zakat starts at 2012 to 2013. Meanwhile, two other institution have always experienced efficient. Keywords: Efficiency, Amil Zakat Institution, Data Envelopment Analysis (DEA)